Storage method for prolonging calendar life of composite manganese lithium ion battery
By controlling the state of charge and storage temperature of the composite manganese-based lithium-ion battery, the problem of SEI film thickening caused by Mn2+ dissolution was solved, thereby improving the battery's calendar life and electrical performance.
Patent Information
- Application Number
- CN202511186255.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-23
- Publication Date
- 2025-11-28
AI Technical Summary
The short calendar life of composite manganese-based lithium-ion batteries is mainly due to the side reaction caused by the dissolution of Mn2+ during storage of lithium manganese oxide and lithium manganese iron phosphate, which forms a thick SEI film, resulting in reduced capacity and increased internal resistance.
Controlling the state of charge of the composite manganese-based lithium-ion battery to 50%-100% SOC and storing it at ≤25℃ reduces the dissolution of Mn2+, decreases SEI film thickening, and improves battery life.
By controlling the state of charge and storage temperature, Mn2+ dissolution is reduced, extending the battery's calendar life and maintaining good electrical performance.
Smart Images

Figure CN121035394A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium ion batteries, in particular to a storage method for improving the calendar life of a composite manganese-based lithium ion battery. BACKGROUND
[0002] In recent years, the new energy industry has developed rapidly, and lithium ion batteries have an absolute market advantage in application fields represented by electric vehicles and consumer electronics. Electric light vehicles represented by electric bicycles are an important market for lithium ion batteries to replace lead-acid batteries. Due to the cost sensitivity of this market, low-cost lithium manganate and lithium iron phosphate are the main application of lithium ion battery cathode materials.
[0003] Lithium manganate has the advantages of low cost, high rate performance, and good low temperature performance. Lithium manganese iron phosphate has an olivine structure similar to lithium iron phosphate, and has the advantages of high safety, long life, and low cost. The composite manganese-based lithium ion battery made by mixing lithium manganate and lithium manganese iron phosphate has the advantages of low cost, high safety, long life, and good low temperature performance, and becomes an important direction of electric light vehicle batteries.
[0004] However, both lithium manganate and lithium manganese iron phosphate have poor storage performance, which results in the short calendar life of the composite manganese-based lithium ion battery. This is because there is Mn2+ dissolution in the two materials during battery storage, and the side reaction of Mn2+ with the electrolyte leads to the loss of lithium ions, forming a thicker SEI film, which causes the capacity of the battery to decrease and the internal resistance to increase.
[0005] Currently, the methods for improving the calendar life of lithium manganate and lithium manganese iron phosphate in the industry mainly focus on coating, doping modification of the two kinds of cathode materials, and optimization of the electrolyte. The present application sets appropriate cell storage conditions to reduce the dissolution of Mn2+ in manganese-based cathode materials, and obtains a simple and feasible storage method for improving the calendar life of a composite manganese-based lithium ion battery. SUMMARY
[0006] The present application aims to provide a storage method for improving the calendar life of a composite manganese-based lithium ion battery to solve the problems raised in the background art.
[0007] To achieve the above-mentioned purpose, the present application provides the following technical solution: a storage method for improving the calendar life of a composite manganese-based lithium ion battery, wherein the composite manganese-based lithium ion battery is charged to a state of charge (SOC) of 50%-100% before storage, and the cell storage environment temperature is controlled to be less than or equal to 25℃.
[0008] The positive electrode active material of the composite manganese lithium-ion battery contains lithium manganese oxide and lithium manganese iron phosphate, with the two materials accounting for ≥60% of the mass of the positive electrode active material. The remaining positive electrode active material is one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based solid solution.
[0009] The lithium manganese oxide has a spinel structure and the chemical formula is LiMn2O4.
[0010] The lithium manganese iron phosphate has an olivine structure and the chemical formula is LiMnxFe(1-x)PO4, where x = 0.6-0.8.
[0011] The voltage range of the manganese-based lithium-ion battery is 2.7-4.2V.
[0012] When the composite manganese-based lithium-ion battery is charged to a state of charge of 50%-100%, the open-circuit voltage of the battery after charging is 3.85V-4.20V.
[0013] The temperature of the storage environment for the control cell is 0-25℃.
[0014] Compared with the prior art, the beneficial effects of the present invention are:
[0015] This invention controls the state of charge (SOC) of the composite manganese-based lithium-ion battery to 50%-100%, resulting in a relatively low lithium intercalation amount in the cathode material of the cell. At this point, the Mn element has a higher valence state. 2+ The dissolution problem was significantly reduced; in addition, high temperature promoted the dissolution of Mn. 2+ This method also mitigates Mn dissolution by controlling the cell storage environment temperature, a crucial factor in leaching. 2+ Dissolution issues. Considering the control of cell state of charge and storage environment temperature, the dissolution of Mn in composite manganese-based lithium-ion batteries during storage is a concern. 2+ Reduced dissolution alleviates Mn 2+ The problem of SEI film thickening caused by electrolyte decomposition is mitigated, which reduces cell capacity decay and internal resistance increase, improves battery calendar life, and maintains good electrical performance after long-term storage. Attached Figure Description
[0016] Figure 1 This describes the battery capacity change of the battery cell in Embodiment 1 of the present invention after different SOCs and storage times at 25°C.
[0017] Figure 2 The change in battery internal resistance of the battery cell in Embodiment 1 of the present invention after different SOCs and storage times at 25°C;
[0018] Figure 3 This illustrates the battery capacity changes of the battery cell at different SOCs and storage times at 45°C in Embodiment 1 of the present invention.
[0019] Figure 4 Battery resistance change after storage of Example 1 of the application at 45℃ for different SOC and storage time;
[0020] Figure 5 0.5C charging performance comparison after storage of Example 1 of the application for different state of charge batteries;
[0021] Figure 6 1C discharge performance comparison after storage of Example 1 of the application for different state of charge batteries;
[0022] Figure 7 Battery capacity change after storage of Example 2 of the application at 25℃ for different SOC and storage time;
[0023] Figure 8 Battery resistance change after storage of Example 2 of the application at 25℃ for different SOC and storage time. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only some of the embodiments of the application, but not all the embodiments of the application.
[0025] A storage method for improving the calendar life of a composite manganese lithium ion battery, before storage, the composite manganese lithium ion battery is charged to a state of charge of 50%-100% SOC, and the storage environment temperature of the battery cell is controlled to be ≤25℃.
[0026] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0027] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0028] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0029] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0030] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0031] In the composite manganese lithium ion battery, the positive active material contains lithium manganate and lithium manganese iron phosphate materials, the mass ratio of the two materials in the positive active material is ≥60%, and the remaining positive active material is one of lithium cobaltate, lithium nickel cobalt manganate, lithium nickel cobalt aluminumate, and lithium-rich manganese-based solid solution.
[0032] Example 1
[0033] Please see Figures 1-6 A storage method to improve the calendar life of composite manganese-based lithium-ion batteries:
[0034] (1) 240 cylindrical 4Ah composite manganese lithium-ion batteries were selected. The main active materials of the positive electrode of the battery cell were 70%wtLiMn2O4 and 30%wtLiMn0.6Fe0.4PO4. The charge and discharge voltage range of the battery cell was 2.7-4.2V.
[0035] (2) Divide the 90 battery cells into two groups, A and B, with 120 cells in each group. The storage temperature of the cells in group A is set to 25±2℃; the storage temperature of the cells in group B is set to 35±2℃; and the storage temperature of the cells in group C is set to 45±2℃.
[0036] (3) Divide each group of cells A and B into four groups: A, B, C and D, with 30 cells in each group. Set the storage time to 15 days, 30 days, 60 days and 90 days.
[0037] (4) Divide the 30 cells in each group A, B, C, and D into 10 groups ①-⑩, with 3 cells in each group. Set the state of charge (SOC) of the cells in groups ①-⑩ after charging to 10%, 20%, 30%, ... 100%, and clearly mark the serial number of each cell to correspond to the storage temperature, storage time, and state of charge.
[0038] (5) Before storage, all cells with x% SOC (x = 10, 20, 30...100) of charge stored shall be charged, discharged and tested in the following manner:
[0039] ① Discharge at a constant current of 0.5C to 2.7V at 25±2℃, and let stand for 10 minutes;
[0040] ② Charge to 4.2V with a constant current and voltage of 0.5C, cut off current of 0.05C; let stand for 10 minutes;
[0041] ③ Discharge the battery at a constant current of 0.5C to 2.7V and record the initial battery capacity C0;
[0042] ④ Charge the battery cell with a constant current of 0.5C for 1.2x min (x = 10, 20, 30...100); ⑤ After standing for 6 hours, test the initial voltage U0 and internal resistance R0 of the battery cell.
[0043] (6) The batteries charged to the specified state of charge are stored in an oven at a specified ambient temperature according to their groups. After the storage period, the oven is removed and the batteries are left to stand at 25±2℃ for 6 hours before the following tests are performed:
[0044] ① Test the voltage U1 and internal resistance R1 of the battery cell after storage, and calculate the internal resistance growth rate = (R1-R0) / R0;
[0045] ② Discharge at a constant current of 0.5C to 2.7V at 25±2℃, and let stand for 10 minutes;
[0046] ③ Charge to 4.2V with a constant current and voltage of 0.5C, cut off current of 0.05C; let stand for 10 minutes;
[0047] ④ Discharge the battery at a constant current of 0.5C to 2.7V, record the recovered capacity C1, and calculate the capacity retention rate = C1 / C0.
[0048] Test results are as follows Figures 1-4 As shown.
[0049] from Figures 1-4 The test results show that the capacity retention rate of batteries with a state of charge (SOC) of 50%-100% is higher than that of batteries with a SOC of 10%-40% after storage at 25℃ and 45℃, while the internal resistance growth rate is lower for batteries with a SOC of 50%-100% than for batteries with a SOC of 10%-40%. Furthermore, for batteries with the same state of charge and storage time, the capacity retention rate at 25℃ is significantly higher than that at 45℃, and the internal resistance growth rate is also significantly lower.
[0050] Considering the potential deterioration of battery rate performance due to increased internal resistance, battery cells stored at 25°C for 90 days at 20% and 50% SOC were selected for charge-discharge testing. The test method is as follows:
[0051] ① 0.5C charging test: Discharge to 2.7V with a constant current of 0.5C at 25±2℃, and let stand for 10 minutes; charge to 4.20V with a constant current and constant voltage of 0.5C, and cut off the current at 0.05C; let stand for 10 minutes; discharge to 2.7V with a constant current of 0.5C at 25±2℃, and record the discharge capacity C0; let stand for 10 minutes; charge to 4.20V with a constant current of 0.5C at 25±5℃; let stand for 10 minutes; discharge to 2.7V with a constant current of 0.5C at 25±5℃, record the capacity C0.5, and calculate C0.5 / C0.
[0052] ② 1C discharge test: Discharge to 2.7V with a constant current of 0.5C at 25±5℃, and let stand for 10 minutes; charge to 4.20V with a constant current and constant voltage of 0.5C, and cut off current of 0.05C; let stand for 10 minutes; discharge to 2.7V with 1C at 25±5℃, record the capacity C1, and calculate C1 / C0.
[0053] Test results are as follows Figures 5-6 As shown;
[0054] The battery charge and discharge test results after storage at 25°C for 90 days with 20% SOC and 50% SOC are as follows: Figure 5 and Figure 6 The charging voltage plateau of a 50% SOC storage battery is lower than that of a 20% SOC storage battery, while the constant current charging capacity ratio of a 50% SOC storage battery is higher than that of a 20% SOC storage battery. The discharge voltage plateau of a 50% SOC storage battery is also higher than that of a 20% SOC storage battery; these results indicate that the charge / discharge performance of a 50% SOC storage battery is superior to that of a 20% SOC storage battery.
[0055] Example 2
[0056] Please see Figures 7-8 A storage method to improve the calendar life of composite manganese-based lithium-ion batteries:
[0057] (1) 72 cylindrical 5Ah composite manganese lithium-ion batteries with a cell positive electrode active material of 45%wtLiMn2O4, 30%wtLiMn0.6Fe0.4PO4 and 25%wtLiNi0.83Co0.12Mn0.05O2, and the cell charge and discharge voltage range is 2.7-4.2V.
[0058] (2) Divide the 144 batteries into four groups: A, B, C, and D, with 18 cells in each group. Set the state of charge after charging to 25%, 50%, 75%, and 100%.
[0059] (3) Divide the 36 cells in each group A, B, C and D into 6 groups, with 3 cells in each group. The storage time for the cells in the 6 groups is set to 1 month, 2 months, 3 months...6 months respectively. The serial number of each cell is clearly marked and can correspond to the state of charge and storage time.
[0060] (4) Before storage, all cells with x% SOC (x = 25, 50, 75, 100) of charge stored shall be charged and discharged in the following manner:
[0061] ① Discharge at a constant current of 0.5C to 2.7V at 25±2℃, and let stand for 10 minutes;
[0062] ② Charge to 4.2V with a constant current and voltage of 0.5C, cut off current of 0.05C; let stand for 10 minutes;
[0063] ③ Discharge the battery at a constant current of 0.5C to 2.7V and record the initial battery capacity C0;
[0064] ④ 0.5C constant current charging for 1.2x min (x = 25, 50, 75, 100);
[0065] ⑤ After standing for 6 hours, test the initial voltage U0 and internal resistance R0 of the battery cell.
[0066] (5) Store the batteries charged to the specified state of charge in an oven at a specified ambient temperature according to their groups. After the storage period, remove the oven and let them stand at 25±2℃ for 6 hours before performing the following tests:
[0067] ① Test the voltage U1 and internal resistance R1 of the battery cell after storage, and calculate the internal resistance growth rate = (R1-R0) / R0;
[0068] ② Discharge at a constant current of 0.5C to 2.7V at 25±2℃, and let stand for 10 minutes;
[0069] ③ Charge to 4.2V with a constant current and voltage of 0.5C, cut off current of 0.05C; let stand for 10 minutes;
[0070] ④ Discharge the battery at a constant current of 0.5C to 2.7V, record the recovered capacity C1, and calculate the capacity retention rate = C1 / C0.
[0071] Test results are as follows Figures 7-8 As shown;
[0072] from Figure 7 , Figure 8 The test results show that, within different storage periods, the cell capacity retention rate is the lowest and the internal resistance increases the most at 25% SOC, while the capacity retention rate is higher and the internal resistance increases less at 50% SOC, 75% SOC, and 100% SOC.
[0073] In summary, this invention controls the state of charge (SOC) of the composite manganese-based lithium-ion battery to 50%-100%, resulting in a relatively low lithium intercalation amount in the cathode material. At this SOC, the Mn element has a higher valence state, significantly mitigating Mn²⁺ dissolution. Furthermore, high temperature is a significant factor promoting Mn²⁺ dissolution; this method also mitigates Mn²⁺ dissolution by controlling the cell storage environment temperature. By combining the control of cell SOC and storage environment temperature, the composite manganese-based lithium-ion battery exhibits reduced Mn²⁺ dissolution during storage, mitigating the SEI film thickening caused by Mn²⁺-induced electrolyte decomposition, reducing cell capacity decay and internal resistance increase, improving battery calendar life, and maintaining good electrical performance after long-term storage.
[0074] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
Claims
1. A storage method for improving the calendar life of composite manganese-based lithium-ion batteries, characterized in that, Before storage, charge the composite manganese-based lithium-ion battery to 50%-100% SOC, and control the storage environment temperature of the cell to ≤25℃.
2. The storage method for improving the calendar life of a composite manganese-based lithium-ion battery according to claim 1, characterized in that: The positive electrode active material of the composite manganese-based lithium-ion battery contains lithium manganese oxide and lithium iron manganese phosphate, with the two materials accounting for ≥60% of the mass of the positive electrode active material. The remaining positive electrode active material is one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based solid solution.
3. The storage method for improving the calendar life of a composite manganese lithium-ion battery according to claim 2, characterized in that: The lithium manganese oxide has a spinel structure and the chemical formula is LiMn2O4.
4. The storage method for improving the calendar life of a composite manganese-based lithium-ion battery according to claim 2, characterized in that: The lithium manganese iron phosphate has an olivine structure and the chemical formula is LiMnxFe(1-x)PO4, where x = 0.6-0.
8.
5. The storage method for improving the calendar life of a composite manganese lithium-ion battery according to claim 1, characterized in that: The voltage range of the manganese-based lithium-ion battery is 2.7-4.2V.
6. The storage method for improving the calendar life of a composite manganese-based lithium-ion battery according to claim 1, characterized in that: When the composite manganese-based lithium-ion battery is charged to 50%-100% SOC, the open-circuit voltage of the battery after charging is 3.85V-4.20V.
7. The storage method for improving the calendar life of a composite manganese lithium-ion battery according to claim 1, characterized in that: The controlled storage environment temperature for the battery cells is 0-25℃.